Medical secrecy: low, medical and deontological aspects - Білецька, Г. А.; Ковальова, Я. О. (Theory and practice of jurisprudence, 2016)
Strengthening recent years the legal and public control of medical activities do not disregard the legal regulation of medical law as an institution of medical information as well as questions of law in violation of the rights of a citizen guaranteed to preserve secret information ascribed to medical confidentiality, persons committed to bound to respect it. The purpose of this study was dividing of medical and legal features of the use of the concept of "medical secret" in the practice and regulations. The modern concept of medical confidentiality was recorded in the International Code of Medical Ethics, which has existed since 1949, and in Ukraine - Oath physician, approved by the Decree of the President of Ukraine № 349 of June 15, 1992 year. Feature medical information that distinguishes the institution from other concepts of ethics, is that the safety of medical confidentiality is guaranteed in law. Today its protection legislation provided by the establishment of certain prohibitions and legal responsibility for its disclosure. Therefore, there are rules for the use of this information that secured in laws of Ukraine "Fundamentals of Ukraine on Health Care", "On Information", Civil and Criminal Codes. Disclosure of information that is of medical confidentiality, without consent is lawful if: for the purposes of examination and treatment of a citizen who is unable to because of his condition to express their will; the threat of the spread of infectious diseases, mass poisonings and damage; at the request of the inquiry and investigation, the prosecutor and the court in connection with the investigation or trial; when assisting a minor under the age of 14 years to inform his parents or legal representatives; if there are reasons that suggest that the injury caused to the citizen as a result of unlawful acts; in the interests of national security, economic prosperity and human rights; in the interests of national security, territorial integrity or public safety; medical examination at brides who are obliged to inform each other about their health; in the case of dismissal of a patient with active tuberculosis of the penitentiary system in order to make this body Health released the selected place of residence; in the case of HIV infection in minor under 18, as well as those found in the manner prescribed by law incapable to notify the parents or legal representatives of these persons; with address of the victim of an accident without a referral company reported the company (which employs a victim) or the place of the accident with a person self-employed. Thus, knowledge of doctors and lawyers specifics about the ethical and legal aspects of the issue of preservation of medical confidentiality is extremely important. Breach medical confidentiality reasons, we think first of all is ignorance of the law and a lack of understanding the harm that can be inflicted, violating the principle of confidentiality.